Changes in gut flora in patients with epilepsy: a systematic review and meta-analysis - He, Xingyan; Zhang, Yuxin (Frontiers in Microbiology, 2024)
BackgroundEpilepsy is a prevalent chronic neurological disorder that is strongly associated with a wide range of psychological, cognitive and social problems. It affects a significant proportion of the global population and has a number of complex etiologies. A growing body of research indicates that there is a strong association between epilepsy and the gut microbiota. Indeed, a substantial body of research has investigated the potential role of epilepsy in relation to the gut microbiota, examining alterations in the abundance, diversity, and relative abundance of the gut microbiota in patients with epilepsy.MethodsThis study was conducted in accordance with the PRISMA guidelines and included multiple studies that met specific criteria. A keyword search was conducted in the following databases: PubMed, Embase, and Web of Science. The data extraction and quality assessment were conducted by two independent researchers. A systematic review and meta-analysis of the relationship between patients with epilepsy and gut flora was conducted using the R 4.3.4 software.ResultsThe results of the analyses indicated that the intestinal flora of patients with epilepsy did not differ significantly in alpha diversity compared to healthy controls. However, the relative abundance of specific flora, such as Verrucomicrobia and Ackermannia was significantly increased in patients, whereas Lactobacillus was significantly decreased.ConclusionThe relationship between epilepsy and gut flora is reciprocal. The present meta-analysis demonstrated that there were no statistically significant alterations in the overall characteristics of the intestinal flora of the patients. However, significant changes were observed in the relative abundance of certain phyla and genera. Consequently, it is hypothesized that epilepsy can cause changes in the relative abundance of specific flora in patients. Furthermore, in conjunction with previous studies, it is believed that changes in intestinal flora can also have an effect on seizures. For example, Lactobacillus may be a beneficial genus that potentially reduces seizures. Conversely, the effect of Akkermansia is two-sided.